1985
DOI: 10.2527/jas1985.613702x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sorghum Grain Variety and Reconstitution on Site and Extent of Starch and Protein Digestion in Steers

Abstract: Hetero-yellow (HY), red (RED) and brown (BR, high tannin) sorghums were fed dry-rolled or reconstituted (RED and BR only) to evaluate the effect of variety and reconstitution on the site and extent of starch and protein digestion in steers fitted with ruminal, duodenal and ileal cannulae. Processed grains were incorporated into 88% sorghum (DM basis) diets fed at 2% of body weight in a 5 X 5 Latin square. Ruminal fermentation of organic matter, starch and protein tended to be lower for the dry-rolled RED than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
12

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 0 publications
1
21
0
12
Order By: Relevance
“…Este fato era esperado, pois já existem resultados semelhantes publicados para aves (Mitaru et al, 1983;Grigoletto et al, 2003), suínos (Cousins et al, 1981;Myer et al, 1986;Patricio et al, 2003) e ruminantes (Hibberd et al 1985;Streeter et al, 1990).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Este fato era esperado, pois já existem resultados semelhantes publicados para aves (Mitaru et al, 1983;Grigoletto et al, 2003), suínos (Cousins et al, 1981;Myer et al, 1986;Patricio et al, 2003) e ruminantes (Hibberd et al 1985;Streeter et al, 1990).…”
Section: Resultsunclassified
“…Da mesma forma, Santos et al (2002), em eqüinos, não verificaram efeito positivo do uso de grãos ensilados de milho em relação aos grãos secos de milho sobre este parâmetro. Contudo, têm-se verificado resultados diferentes em grande parte das pesquisas com outras espécies animais (Aguirre, 1984;Crenshaw et al, 1984;Hibberd et al, 1985;Defoor et al, 2001).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Zinn et al (2002) summarized available literature and suggested that post-ruminal starch digestion appears to be limited by accessibility of the amylolytic enzymes and not limitations in the amount of enzymes. It is Karr et al (1966), Hibberd et al (1985), Axe et al (1987), Zinn (1988Zinn ( , 1989Zinn ( , 1990Zinn ( , 1991, Streeter et al (1989Streeter et al ( , 1990Streeter et al ( , 1991, Hill et al (1991), Palmquist et al (1993), Streeter and Mathis (1995), Swingle et al (1999), Theurer et al (1999), Garcia et al (2000).…”
Section: Optimizing Site Of Digestion Advantagesmentioning
confidence: 99%
“…Similarly, Hibberd et al (1985) observed that HMCS showed greater in vitro and in vivo digestibility, when compared to dry grains.…”
Section: Resultsmentioning
confidence: 91%